Hubungan Self Efficacy dengan Tingkat Stress .dalam Menyusun Tugas AKhir (SKRIPSI) - Intan Dwi Kriswanti; Arifin Nur Budiono; Fakhruddin Mutakin (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2020)
Research on the relationship of self efficacy with stress levels in compiling the final project (thesis) FKIP .Islamic University Jember Year 2016 .Batch  Year with 31 students surveyed. The method used for data collection .ncludes observation, interviews and questionnaires, the analysis used is Product Moment correlation analysis. Based on the observation results obtained a description of the psychology of students when preparing their thesis, followed by interviews with 8 FKIP students, there were 6 students who experienced stress when facing thesis. The distribution of questionnaires to 31 students was continued, as many as 8 students in the category of high self-efficacy and moderate stress, 5 students in the category of moderate and high stress self-efficacy, and 18 students in the category of moderate self-efficacy and moderate stress. In this study students who are preparing the final project are in the medium category, meaning that between self efficacy and stress faced by balanced students. This proves that between self efficacy and stress levels students have a relationship. Keywords :Self Efficacy, Student Stress